Probing the Roughness of Porphyrin Thin Films with X-ray Photoelectron Spectroscopy - Kataev, Elmar; Wechsler, Daniel; Williams, Federico J.; Köbl, Julia; Tsud, Natalia; Franchi, Stefano; Steinrück, Hans-Peter; Lytken, Ole (ChemPhysChem, 2020)
Thin-film growth of molecular systems is of interest for many applications, such as for instance organic electronics. In this study, we demonstrate how X-ray photoelectron spectroscopy (XPS) can be used to study the growth behavior of such molecular systems. In XPS, coverages are often calculated assuming a uniform thickness across a surface. This results in an error for rough films, and the magnitude of this error depends on the kinetic energy of the photoelectrons analyzed. We have used this kinetic-energy dependency to estimate the roughnesses of thin porphyrin films grown on rutile TiO2(110). We used two different molecules: cobalt (II) monocarboxyphenyl-10,15,20-triphenylporphyrin (CoMCTPP), with carboxylic-acid anchor groups, and cobalt (II) tetraphenylporphyrin (CoTPP), without anchor groups. We find CoMCTPP to grow as rough films at room temperature across the studied coverage range, whereas for CoTPP the first two layers remain smooth and even; depositing additional CoTPP results in rough films. Although, XPS is not a common technique for measuring roughness, it is fast and provides information of both roughness and thickness in one measurement.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Growth; Porphyrin molecules; Thin films; X-ray photoelectron spectroscopy